Surface Segregation in Lanthanum Strontium Manganite Thin Films and Its Potential Effect on the Oxygen Reduction Reaction. Issue 10 (19th July 2017) - Davis, J. N.; Ludwig, K. F.; Smith, K. E.; Woicik, J. C.; Gopalan, S.; Pal, U. B.; Basu, S. N.
Abstract : A limiting factor for solid oxide fuel cell (SOFC) performance is the oxygen reduction reaction (ORR) that occurs at the cathode surface. This study examines changes in the surface composition of (La0.8 Sr0.2 )0.95 MnO3 (LSM-20), a well-known SOFC cathode material. Heteroepitaxial thin films of LSM-20 were grown on lattice matched single crystal LaAlO3 and NdGaO3 substrates. Total Reflection X-ray Fluorescence (TXRF) measurements showed surface manganese enrichment on annealing at 800°C in air. X-ray absorption near edge spectroscopy (XANES) showed that this leads to a redistribution of manganese 3+, 4+, and 2+ valence states at the surface. This was confirmed by defect modeling, which showed that surface Mn segregation leads to an increase in the surface concentration of oxygen vacancies and the Mn +4 species, both of which are expected to be beneficial for ORR.